2020 International Electronics Symposium (IES) 2020
DOI: 10.1109/ies50839.2020.9231619
|View full text |Cite
|
Sign up to set email alerts
|

Risk Diagnosis and Mitigation System of COVID-19 Using Expert System and Web Scraping

Abstract: The Novel Coronavirus that just appeared at the end of 2019 was named SARS-COV-2 which caused a pandemic of a respiratory disease known as COVID-19. In Indonesia itself, there was a case of COVID-19 first announced on March 2, 2020. The spread of COVID-19 in Indonesia is so fast because of one factor namely the lack of knowledge about COVID-19 prevention and early detection. This study will discuss the system to provide the latest information about the development of the COVID-19 case in Indonesia and help the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In the present scoping review, the results of 16 studies identified a positive impact on a diagnosis of COVID-19 with the assistance of CDSS based on ES. 5,17,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In the reviewed studies, rule sets were the most common methods in developing a knowledge base of CDSS. 5,17,88,89,93,94,96,97 Rule-based systems acquire contextual knowledge from extracted data stored and manipulated in other approaches.…”
Section: Knowledge-based Cdssmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present scoping review, the results of 16 studies identified a positive impact on a diagnosis of COVID-19 with the assistance of CDSS based on ES. 5,17,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In the reviewed studies, rule sets were the most common methods in developing a knowledge base of CDSS. 5,17,88,89,93,94,96,97 Rule-based systems acquire contextual knowledge from extracted data stored and manipulated in other approaches.…”
Section: Knowledge-based Cdssmentioning
confidence: 99%
“…101 The reviewed studies extracted data from various sources, such as observed symptoms, specific medical measurements, pre-existing medical conditions or any hospitalization history, recent PCR test results, clinical guidelines, websites (e.g., WHO), and knowledge of experts to develop rule sets. 5,17,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] Therefore, knowledge-based CDSS in these studies can provide a comprehensive view of the patient's health information. This feature enables health practitioners to access treatment recommendations and risk classification, recommend test lists, quickly track test results and symptoms, and access clinical guidelines in the COVID-19 pandemic.…”
Section: Knowledge-based Cdssmentioning
confidence: 99%
See 2 more Smart Citations
“…Mufid et al developed an Android app that consists of an expert system for early detection of having COVID-19 and an information module that displays current news about the spread of the virus [25]. The app was tailored specifically for Indonesia.…”
Section: Related Workmentioning
confidence: 99%